THE EFFECT OF ONLINE CUSTOMER REVIEW ON TRUST THAT AFFECT DND PET CONSUMERS’ BUYING INTENTION IN SHOPEE MARKETPLACE: THE EFFECT OF ONLINE CUSTOMER REVIEW ON TRUST THAT AFFECT DND PET CONSUMERS’ BUYING INTENTION IN SHOPEE MARKETPLACE - Soekotjo, Edward (PERFORMA, 2022)
The purpose of this research is to find out whether the effect of Online Customer Review on trust that affects DND PET consumers’ buying intention in Shopee marketplace. This research method uses Partial Least Square (PLS) data analysis method with SmartPLS software.The sample that is use in this research is DND Pet followers in Shopee with the number of 282 respondents. Data collection technique uses questionnaire that is distributed by using Google Form with Likert Scale measurement. Based on data analysis, it can be concluded that Online Customer Review (X) has significant effect on trust (Y), trust (Y) has significant effect on buying intention (Z), and trust (Y) mediates the effect of Online Customer Review (X) on buying intention (Z). Keywords: Online Customer Review, Trust, Buying Intention